(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
Jair Bolsonaro recently ratified Medida Provisória n. 870, which transfers the competence to define the boundaries of indigenous lands from the current incumbent, Fundação Nacional do Indo (FUNAI), to the Ministry of Agriculture. The Minister of Agriculture, Tereza Cristina Corrêa da Costa Dias, represents the agricultural landlords who have an interest in increasing the land devoted to grazing and soybean cultivation. This decision endangers and disadvantages all the indigenous people, especially those living in Amazonia